International Students' Perceptions and Experiences of British Drinking Cultures. (September 2018) - Thurnell-Read, Thomas; Brown, Lorraine; Long, Philip
While the increased scale and importance of international students to the UK Higher Education sector is now well established, little is known about the ways in which students from non-UK countries experience and interact with the heavy drinking culture that predominates on and near many British universities. Drawing on qualitative interviews, this article analyses the perceptions, attitudes, and experiences of British drinking cultures held by international students studying on postgraduate courses at a UK university. Students report prior awareness of alcohol consumption being important to British culture and recount both positive and negative experiences of witnessing and, for many, participating in drinking alcohol. Students make ready comparisons with the drinking habits and attitudes of their own culture. Further still, many made a distinction between the public house, or 'pub', as a welcoming and friendly social space, and bars and nightclubs, where a far greater risk of exposure to violence and harassment was perceived. The article provides theoretical insights to support future and more wide-ranging research into mobile drinking cultures and also suggests practical implications to inform stakeholders with interests in the welfare of international students in the UK in relation to the provision of effective and proactive policies which address the impact of British drinking cultures on international student integration and well-being.